2007
DOI: 10.1177/1087054706292106
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Performance Test (CPT) of College Students With ADHD, Psychiatric Disorders, Cognitive Deficits, or No Diagnosis

Abstract: The CPT reliably differentiated between individuals with ADHD and both normal college students and individuals with psychiatric diagnoses but not persons with learning/cognitive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 13 publications
7
67
1
Order By: Relevance
“…For the last several years, our laboratory has been conducting research in undergraduates with ADHD to try to understand the cognitive effects of stimulant medications (Advokat et al, 2007;Advokat et al, 2008;Advokat & Luo, unpublished;Barrilleaux & Advokat, 2009). Given evidence that suggests there is a positive relationship between the Grade Point Average of undergraduates and their working memory (Gropper & Tannock, 2009) our efforts to clarify the cognitive actions of these drugs include studies of both, neuropsychological and academic performance of adult ADHD-diagnosed undergraduates.…”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%
“…For the last several years, our laboratory has been conducting research in undergraduates with ADHD to try to understand the cognitive effects of stimulant medications (Advokat et al, 2007;Advokat et al, 2008;Advokat & Luo, unpublished;Barrilleaux & Advokat, 2009). Given evidence that suggests there is a positive relationship between the Grade Point Average of undergraduates and their working memory (Gropper & Tannock, 2009) our efforts to clarify the cognitive actions of these drugs include studies of both, neuropsychological and academic performance of adult ADHD-diagnosed undergraduates.…”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%
“…Individuals with ADHD tend to experience more marital and family problems compared with normal adults. They may have higher divorce rates and greater risks of substance misuse, driving accidents, sexual problems, and job changes than adults without ADHD (Advokat et al 2007;Cox et al 2011;Rosenbloom and Wultz 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while some studies have supported relationships between ADHD and difficulties with inhibition, attention, and working memory (Antshel et al, 2010;Epstein et al, 1998;Forbes, 1998;Gropper and Tannock, 2009), the effect sizes have been moderate, and many individuals with ADHD did not show executive dysfunction (Nigg, 2013;Willcutt et al, 2005). Most of the executive functioning measures were reliant on processing speed (Advokat et al, 2007;Lipszyc and Schachar, 2010), and several studies suggested that slower reaction times and reaction time variability were more strongly associated with ADHD than actual omission, commission, or other outright executive functioning errors (Advokat et al, 2007;Alderson et al, 2007;Bedard and Tannock, 2008;Metin et al, 2013). Working memory difficulties appeared a bit more consistent according to some meta-analyses (Kasper et al, 2012;Martinussen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%